1.
√121 -10√6,4 *√0,1=11 - √16*√0,4*√0,1=11 - 4√0,04=11-4*0,2=11-4,2=6,8
2√5 -√45 +√80=2√5 - √(9*5)+√(16*5)=2√5-3√5+4√5=3√5
2.
2√5 -√45 +80=2√5 - √(9*5)+80=2√5 -3√5+80=80 - √5
(√a+√b)(√a -b)+b=a -b√a+√ab+b
(если тут упустили во второй скобке √b, то будет так
(√a+√b)(√a-√b)+b=a-b+b=a - вот тут упрощается.)
3.
4.
![\frac{a-3 \sqrt{a} }{a-9} = \frac{ \sqrt{a}( \sqrt{a}-3) }{( \sqrt{a} -3)( \sqrt{a} +3)}= \frac{ \sqrt{a} }{ \sqrt{a}+3 } \frac{a-3 \sqrt{a} }{a-9} = \frac{ \sqrt{a}( \sqrt{a}-3) }{( \sqrt{a} -3)( \sqrt{a} +3)}= \frac{ \sqrt{a} }{ \sqrt{a}+3 }](https://tex.z-dn.net/?f=+%5Cfrac%7Ba-3+%5Csqrt%7Ba%7D+%7D%7Ba-9%7D+%3D+%5Cfrac%7B+%5Csqrt%7Ba%7D%28+%5Csqrt%7Ba%7D-3%29++%7D%7B%28+%5Csqrt%7Ba%7D+-3%29%28+%5Csqrt%7Ba%7D+%2B3%29%7D%3D+%5Cfrac%7B+%5Csqrt%7Ba%7D+%7D%7B+%5Csqrt%7Ba%7D%2B3+%7D)